The Gene Effect of Growth Hormone on Body Weight and Egg Production in Divergent Selection for Five Generation of Japanese Quail (Coturnix coturnix japonica) - Johari, S.; Setiati, N.; Sidadolog, J.H.P.; Hartatik, T.; Yuwanta, T. (International Journal of Poultry Science, 2013)
The aim of this study was to determine the gene effect of Growth Hormone (GH) on divergent selection of Japanese quail. Quails were grouped into high weight (Q-H), low weight (Q-L) and random weight (Q-R) females as a treatment for divergent selection. Parameter phenotype observed in each generation is the weight at four weeks of age and egg production at ten weeks of age for five generations. The results showed that the dominance level on body weight of Q-L was incomplete dominance, Q-R was over dominance and Q-H was lack of dominance. While the dominance level on egg production of Q-L and Q-H were over dominance and Q-R was lack of dominance. The gene effect of GH on body weight of Q-H is 1.53 times greater than the Q-L and 12.37 times greater when compared with Q-R. Whereas the gene effect of GH on egg production of Q-H is 1.53 times greater than the Q-L but only 4 times greater when compared with Q-R. Should be developed that to increase the low-weight (Q-L) is in the BB genotype and the high weight (Q-H) is in the AA genotype groups. Otherwise, to increase the low-weight (Q-L) and high-egg production are in the AA and BB genotypes and the high weight (Q-H) and low-egg production are in the AA and AB genotypes groups.